The effectiveness of emotion-focused couple therapy on coping strategies and internalized shame in nurses with marital conflicts - Deldadeh Mehraban, Mina; Hasanzadeh, Ramezan; Mirzaian, Bahram (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Family is the first and most important social institution, and a healthy society depends on having a healthy couple who strive to achieve their goals with a suitable level of marital satisfaction. The present study aimed to determine the effectiveness of emotion-oriented couple therapy on coping strategies and internalized shame in nurses with marital conflicts. Methods: The current research method is a quasi-experimental one with a pre-test-post-test design and a one-month follow-up with the control group. The statistical population included all nurses working in Imam Sajjad State Hospital in Ramsar City in 2020. Among these, 30 couples (90 people) were selected by the non-random sampling method available and replaced in the experimental group (emotion-oriented couple therapy) and a control group in a simple random manner (15 couples in each group). Then, 10 sessions of 90 minutes (2 sessions per week) of emotion-oriented couple therapy (Johnson, 2017) were conducted in experimental groups. Data were collected using the internalized shame and coping strategies questionnaire. The data was analyzed using SPSS-24 software and through the analysis of variance test with repeated measurements. Results: The research results showed that emotion-oriented couple therapy is effective on coping strategies (P